Application of Acidifier in Drinking Water on Broiler Chicken Carcass Weight - Esti, Risma Novela (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2024)
This study aims to study the effects of adding acidifier at different levels on carcass weight and carcass weight persentage of broiler chickens. The study used 100 DOC unsexed Lohmann MB-202 strains that were grouped into 4 treatment groups. Each treatment was repeated 5ntimes and each replication used 5 broiler chickens. The treatment group consisted of acidifier 0% (P0), acidifier 0,33% (P1), acidifier 0,44% (P2), and acidifier 0,55% (P3). The study was conducted for 4 weeks. The data observed were slaughter weight, carcass weight and percentage carcass of broiler chickens. The data obtained were analyzed by using variance analysis of Compact Random Design (CRD) Pattern Unidirectional and if there were differences between treatments followed by the mean difference test using Duncan's Multiple Range Test (DMRT). The results showed that adding acidifier on water had no effect on slaughter weight, carcass weight and percentage carcass of broiler chickens.